TIPOLOGI KEUANGAN DAERAH KABUPATEN KUBU RAYA TAHUN 2008-2011 - B01106137, Mustapa (Jurnal Pembangunan dan Pemerataan, 2013)
This study entitled " Typology of Kubu Raya regency Financial Year 2008-2011 ". As for the problem of this research is a typology of regional finance How Kubu Raya district . This research uses descriptive method , the research describes the circumstances and events based on the facts fit what happened in the study variables . The author uses time series data , ie data collected over time ( time series ) from various sources to answer the purpose of this thesis . In relation to the discussion of this paper , the authors use the typology Financial Analysis area. Conclusions from this research that there are still areas that have not been healthy financial or backward to the low growth makes pembangunanan Regional Di Kubu Raya district of 12 components in the reception area , 4 of which are included on the receipt that is retarded Retribution , results separated areas of wealth management , fund of tax / non-tax revenue and Emergency Fund . And there are 11 components in the shopping area of ??6 dianataranya backwardness that is included in the category Flowers Shopping , Shopping subsidies , grants Shopping , Shopping for the results of the provincial / district / town & village governments , unexpected shopping , and shopping for goods and services. By creating the advanced economies for the Kubu Raya district , budget management areas more wisely considered very important to make this happen , so make independent financial for the area . And with the creation of human resource capacity and infrastructure to support the proposition economy and encourage economic investment in Kubu Raya District to be more advanced and compete against other regions.